Amniotic Band Sequence, Frequently Misdiagnosed in Cleft Patients - Putri, Nandita Melati; Handayani, Siti; Bangun, Kristaninta (Jurnal Plastik Rekonstruksi, 2012)
Background: Amniotic band sequence (ABS) is a set of congenital malformations attributed to amniotic bands that entangle fetal parts during intrauterine life. thiopatogenesis of this sequence is still unknown. Because of such a wide spectrum of possible anomalies and many combinations of their simultaneous appearance, there are no two identical cases of ABS. This diagnosis is often missed based on the secondary major defects.Patients and Methods : There are cases of cleft patients treated in Plastic Surgery Division Cipto Mangunkusumo Hospital that has other congenital anomalies. The data is taken from the medical record and surgical photos (in our division from 2010-2011). Results : The patients presented had either facial cleft or cleft lip and palate. These patients had other congenital anomalies such as meningoencephalocele and constriction ring syndrome or other defects on the extremities.Summary : This diagnosis may not be often established because we often only see the secondary major defects such as meningoencephalocele or facial cleft. With this paper we hope that we could make this diagnosis known so we can make a multidisciplinary approach to this sequence.